Answer:
Step-by-step explanation:
The ratio is 5:13 and the total number of candy is 18. If the total amount of candy increased by 40x then both candy values would increase by 40x. There are 200 Jolly ranchers and 520 jawbreakers.
You can write it as a proportion and then solve the proportion.
(2.5 hours is 150 minutes)
14 cars x cars
--------------- = -------------------
45 minutes 150 minutes
Then solve.
x=46.6666666
So that is about 47 cars
Answer: ![0.9999](https://tex.z-dn.net/?f=0.9999)
Step-by-step explanation:
Answer:
![AB = \sqrt{a^2 + b^2-2abCos\ C}](https://tex.z-dn.net/?f=AB%20%3D%20%5Csqrt%7Ba%5E2%20%2B%20b%5E2-2abCos%5C%20C%7D)
Step-by-step explanation:
Given:
The above triangle
Required
Solve for AB in terms of a, b and angle C
Considering right angled triangle BOC where O is the point between b-x and x
From BOC, we have that:
![Sin\ C = \frac{h}{a}](https://tex.z-dn.net/?f=Sin%5C%20C%20%3D%20%5Cfrac%7Bh%7D%7Ba%7D)
Make h the subject:
![h = aSin\ C](https://tex.z-dn.net/?f=h%20%3D%20aSin%5C%20C)
Also, in BOC (Using Pythagoras)
![a^2 = h^2 + x^2](https://tex.z-dn.net/?f=a%5E2%20%3D%20h%5E2%20%2B%20x%5E2)
Make
the subject
![x^2 = a^2 - h^2](https://tex.z-dn.net/?f=x%5E2%20%3D%20a%5E2%20-%20h%5E2)
Substitute
for h
becomes
![x^2 = a^2 - (aSin\ C)^2](https://tex.z-dn.net/?f=x%5E2%20%3D%20a%5E2%20-%20%28aSin%5C%20C%29%5E2)
![x^2 = a^2 - a^2Sin^2\ C](https://tex.z-dn.net/?f=x%5E2%20%3D%20a%5E2%20-%20a%5E2Sin%5E2%5C%20C)
Factorize
![x^2 = a^2 (1 - Sin^2\ C)](https://tex.z-dn.net/?f=x%5E2%20%3D%20a%5E2%20%281%20-%20Sin%5E2%5C%20C%29)
In trigonometry:
![Cos^2C = 1-Sin^2C](https://tex.z-dn.net/?f=Cos%5E2C%20%3D%201-Sin%5E2C)
So, we have that:
![x^2 = a^2 Cos^2\ C](https://tex.z-dn.net/?f=x%5E2%20%3D%20a%5E2%20Cos%5E2%5C%20C)
Take square roots of both sides
![x= aCos\ C](https://tex.z-dn.net/?f=x%3D%20aCos%5C%20C)
In triangle BOA, applying Pythagoras theorem, we have that:
![AB^2 = h^2 + (b-x)^2](https://tex.z-dn.net/?f=AB%5E2%20%3D%20h%5E2%20%2B%20%28b-x%29%5E2)
Open bracket
![AB^2 = h^2 + b^2-2bx+x^2](https://tex.z-dn.net/?f=AB%5E2%20%3D%20h%5E2%20%2B%20b%5E2-2bx%2Bx%5E2)
Substitute
and
in ![AB^2 = h^2 + b^2-2bx+x^2](https://tex.z-dn.net/?f=AB%5E2%20%3D%20h%5E2%20%2B%20b%5E2-2bx%2Bx%5E2)
![AB^2 = h^2 + b^2-2bx+x^2](https://tex.z-dn.net/?f=AB%5E2%20%3D%20h%5E2%20%2B%20b%5E2-2bx%2Bx%5E2)
![AB^2 = (aSin\ C)^2 + b^2-2b(aCos\ C)+(aCos\ C)^2](https://tex.z-dn.net/?f=AB%5E2%20%3D%20%28aSin%5C%20C%29%5E2%20%2B%20b%5E2-2b%28aCos%5C%20C%29%2B%28aCos%5C%20C%29%5E2)
Open Bracket
![AB^2 = a^2Sin^2\ C + b^2-2abCos\ C+a^2Cos^2\ C](https://tex.z-dn.net/?f=AB%5E2%20%3D%20a%5E2Sin%5E2%5C%20C%20%2B%20b%5E2-2abCos%5C%20C%2Ba%5E2Cos%5E2%5C%20C)
Reorder
![AB^2 = a^2Sin^2\ C +a^2Cos^2\ C + b^2-2abCos\ C](https://tex.z-dn.net/?f=AB%5E2%20%3D%20a%5E2Sin%5E2%5C%20C%20%2Ba%5E2Cos%5E2%5C%20C%20%2B%20b%5E2-2abCos%5C%20C)
Factorize:
![AB^2 = a^2(Sin^2\ C +Cos^2\ C) + b^2-2abCos\ C](https://tex.z-dn.net/?f=AB%5E2%20%3D%20a%5E2%28Sin%5E2%5C%20C%20%2BCos%5E2%5C%20C%29%20%2B%20b%5E2-2abCos%5C%20C)
In trigonometry:
![Sin^2C + Cos^2 = 1](https://tex.z-dn.net/?f=Sin%5E2C%20%2B%20Cos%5E2%20%3D%201)
So, we have that:
![AB^2 = a^2 * 1 + b^2-2abCos\ C](https://tex.z-dn.net/?f=AB%5E2%20%3D%20a%5E2%20%2A%201%20%2B%20b%5E2-2abCos%5C%20C)
![AB^2 = a^2 + b^2-2abCos\ C](https://tex.z-dn.net/?f=AB%5E2%20%3D%20a%5E2%20%2B%20b%5E2-2abCos%5C%20C)
Take square roots of both sides
![AB = \sqrt{a^2 + b^2-2abCos\ C}](https://tex.z-dn.net/?f=AB%20%3D%20%5Csqrt%7Ba%5E2%20%2B%20b%5E2-2abCos%5C%20C%7D)